HUBUNGAN KEMAMPUAN MENGELOLA EMOSI DENGAN PERILAKU AGRESIF PESERTA DIDIK KELAS XI MIPA SMA N 1 GODONG KABUPATEN GROBOGAN - Kusumaningsih, Yeyen (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Abstract: The research on the relationship between the ability to manage emotions and the aggressive behavior of students was motivated by the discovery of students who vented their emotions through anger, some cried, fought, insulted, mocked, called nicknames and some even acted to hurt someone. This research is a type of quantitative research. Ex post facto research method with a correlational approach. The population used in this study were students of SMA N 1 Godong class XI. used as a try out, namely class XI MIPA 5. While class XI MIPA 1, XI MIPA 2, XI MIPA 3, XI MIPA 4, XI MIPA 6 as the research sample. The sampling used is cluster random sampling technique. The data of this study were obtained through the scale of the ability to manage students' emotions and the scale of students' aggressive behavior. The results of the analysis show the category of ability to manage emotions is very low 1% as many as 2 students. The category of ability to manage emotions is low 33% as many as 35 students. The category of ability to manage emotions is 49% as many as 63 students. The category of ability to manage emotions is high 17% as many as 22 students, while the category of aggressive behavior is very low 32% as many as 37 students. The low category of aggressive behavior is 42% as many as 51 students. The category of moderate aggressive behavior is 22% of 27 students. The category of high aggressive behavior is 4% as many as 5 students. Based on the results of data analysis using product moment analysis, the relationship between the ability to manage emotions and aggressive behavior of students is -0.546, which means that there is a negative relationship between the ability to manage emotions and aggressive behavior, and the level of relationship between these variables is in the medium category. Based on the results of this study, the suggestion that can be conveyed is that BK teachers are able to provide services to improve the ability to manage students' emotions Keywords: Ability to Manage Emotions, Aggressive Behavior.